2013
DOI: 10.1016/j.ijcard.2012.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of exercise training in pulmonary arterial hypertension associated with congenital heart disease

Abstract: BACKGROUND: The objective of this prospective study was to assess the efficacy of exercise training as add-on to medical therapy in patients with congenital heart disease associated pulmonary arterial hypertension (CHD-APAH). METHODS: Patients with invasively confirmed CHD-APAH received in-hospital exercise training for 3weeks and continued at home. Efficacy parameters were evaluated at baseline, after 3 and 15weeks. Medical treatment remained unchanged. Worsening events and survival rate were assessed in a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 29 publications
7
123
0
7
Order By: Relevance
“…This was based on a randomized controlled trial (RCT) that demonstrated an improvement (Tables 13 and 14) It is recommended to perform regular follow-up assessments every 3-6 months in stable patients (Table 14) Class a [96,97,99] Achievement/maintenance of a low-risk profile ( in exercise and functional capacity and in quality of life in patients with PH who took part in a training programme as compared with an untrained control group [152]. Since then, additional uncontrolled experiences have supported these data utilising different models of exercise training [153][154][155][156][157]. Two additional RCTs have been published reporting that trained PAH patients reached higher levels of physical activity, had decreased fatigue severity and showed improved 6MWD, cardiorespiratory function and patient-reported quality of life as compared with untrained controls [158,159].…”
Section: Physical Activity and Supervised Rehabilitationmentioning
confidence: 99%
“…This was based on a randomized controlled trial (RCT) that demonstrated an improvement (Tables 13 and 14) It is recommended to perform regular follow-up assessments every 3-6 months in stable patients (Table 14) Class a [96,97,99] Achievement/maintenance of a low-risk profile ( in exercise and functional capacity and in quality of life in patients with PH who took part in a training programme as compared with an untrained control group [152]. Since then, additional uncontrolled experiences have supported these data utilising different models of exercise training [153][154][155][156][157]. Two additional RCTs have been published reporting that trained PAH patients reached higher levels of physical activity, had decreased fatigue severity and showed improved 6MWD, cardiorespiratory function and patient-reported quality of life as compared with untrained controls [158,159].…”
Section: Physical Activity and Supervised Rehabilitationmentioning
confidence: 99%
“…44 Future studies are needed to determine whether these favorable effects of exercise training can translate into a reduction in long-term major adverse clinical outcomes. 14,[17][18][19][20][21][22]27,29 and peak absolute oxygen uptake (mL/min) on pooled analysis of included studies (n=6, B). 14,[19][20][21]27 The mechanisms underlying improvement in exercise tolerance with exercise training among patients with pulmonary hypertension are not well understood.…”
Section: Pandey Et Al Exercise Training In Pulmonary Hypertension 1039mentioning
confidence: 99%
“…Several small studies have evaluated exercise training as an adjunctive therapeutic strategy in patients with chronic pulmonary hypertension. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Although most of these studies were small and not designed to address clinical end points, such as mortality or hospitalizations, related to pulmonary hypertension, they have demonstrated a variable degree of improvement in exercise tolerance and quality of life in response to training.Therefore, because of the uncertainty about the benefit of structured exercise training programs in patients with pulmonary hypertension, we performed this systematic review and meta-analysis to assess the efficacy and safety of structured exercise training regimens in patients with pulmonary hypertension. …”
mentioning
confidence: 99%
“…However, recent evidence suggests almost universal benefit from regular aerobic conditioning in associated diseases, including other types of PAH and left heart disease. 38,39 A small nonrandomized cohort study of a mixed PAH-CHD sample, half with ES, reports that conditioning is safe and may be effective 40 ; European guidelines support a possible role for supervised exercise rehabilitation in deconditioned patients with PAH, without a distinction based on the presence of CHD (class IIa). 27 Recommendations defining optimal exercise type, intensity, and potential efficacy await further investigation (eg, NCT01397110 at clinicaltrials.gov).…”
Section: Specific Supportive Care For Patients With Esmentioning
confidence: 99%